Understanding the phytochemistry of high-CBD hemp: efficacy of common row cover materials for pollen exclusion and impact on flower phytochemistry - Bowen, Janina K., author; Prenni, Jessica, advisor; Cranshaw, Whitney, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2022)
Production of high-cannabidiol (high-CBD) hemp (Cannabis sativa L.) is steadily increasing in Colorado and across the United States. However, the impact of management practices on flower phytochemistry in this crop remains relatively unexplored. For example, there is high potential for male hemp plants from fiber and grain cultivars to pollinate exclusively female high-CBD hemp plants grown in close proximity, but it is unknown how the cannabinoid content of high-CBD hemp flowers is affected by pollination. We hypothesized that high seed content resulting from pollination will negatively impact the phytochemical yield of high-CBD crops. In this study, three experimental pollen exclusion treatments were applied to two cultivars of high-CBD hemp, 'Cherry Uno' and 'Wife.' Treatments included non-woven thick row cover (largest pore size of approximately 50 microns), non-woven thin row cover (largest pore size approximately 200 microns), woven insect netting (average pore size 700x240 microns), and uncovered controls. A total of 60 high-CBD plants (clones) were planted in a randomized complete block design at the Colorado State University Agricultural Research, Development and Education Center South (ARDEC South) in Fort Collins, Colorado (lat. 40.611804 N; long. -104.997144 W; elevation 1525 meters). Total biomass and seed weights for 60 whole plants were evaluated. Additionally, 5 cm inflorescence samples were taken from each plant, in concordance with the 2019 Colorado Department of Agriculture (CDA) sampling protocol. Seeds and floral material were weighed separately before samples were homogenized in preparation for cannabinoid analysis. Extracts were analyzed by ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) to determine the quantitative profiles of 20 cannabinoids. Results indicate that for the cultivar Cherry Uno, thick and thin row cover treatments effectively reduced pollination as compared to uncovered controls. The row cover treatments did not result in a statistically significant reduction of pollination for cultivar Wife, which may be due to later flowering in this cultivar. For cultivar Cherry Uno, a significant reduction in CBD concentration of up to 2.7% was observed in the heavily seeded controls compared to covered plants (Uncovered control = 3.77% CBD, 0.13% Δ9THC; Thin row cover = 6.49% CBD, 0.21% Δ9THC). Taken together, our results suggest that implementation of strategies to minimize pollination and/or remove seeds from high-CBD hemp biomass could improve cannabinoid yield. More research is warranted to evaluate the economic viability of such strategies and the effectiveness across different cultivars and growing climates.
Keywords: hempseed; phytocannabinoids; UPLC-MS; high-CBD hemp; cannabis; pollen exclusion